COVID-19: Perception of the Pandemic and the Importance of Barrier Measures by the Fruit and Vegetable Sellers of Port-Au-Prince - Benjamin, Francklin; Jean, Katiana; Antoine, Renando; Prou, Marc; Millien, Max; Balthazard-Accou, Ketty; Emmanuel, Evens (European Scientific Journal, ESJ, 2021)
Covid-19 has triggered an unprecedented crisis that not only concerns health, it is also an economic, social, political and possibly humanitarian crisis. In March 2020, the WHO declared the disease to be pandemic and recommended the application of barrier measures. The research question here is to establish the level of social perception of fruit and vegetable sellers of the application of barrier measures in Haiti. This study was based on a mainly qualitative approach. A survey was carried out on a random sample of 50 fruit and vegetable sellers, a vulnerable social category of the metropolitan region of Port-au-Prince (RMPP). 98% of the population studied were women; 92% of them came from rural areas. Only 4% of the respondents declared that they practiced physical distancing versus 96% who declared that they were not able to practice it, or place one of their family members in quarantine. It appears pertinent to grasp, in future, the perception of COVID-19 by the Haitian population on the basis of a comparative approach that places several social classes and several economic activities in the contexts of their respective situations.